An unexpected role of neuroligin-2 in regulating KCC2 and GABA functional switch - Sun, Chicheng (BioMed Central, 2013)
BACKGROUND: GABA(A) receptors are ligand-gated Cl(-) channels, and the intracellular Cl(-) concentration governs whether GABA function is excitatory or inhibitory. During early brain development, GABA undergoes functional switch from excitation to inhibition: GABA depolarizes immature neurons but hyperpolarizes mature neurons due to a developmental decrease of intracellular Cl(-) concentration. This GABA functional switch is mainly mediated by the up-regulation of KCC2, a potassium-chloride cotransporter that pumps Cl(-) outside neurons. However, the upstream factor that regulates KCC2 expression is unclear. RESULTS: We report here that KCC2 is unexpectedly regulated by neuroligin-2 (NL2), a cell adhesion molecule specifically localized at GABAergic synapses. The expression of NL2 precedes that of KCC2 in early postnatal development. Upon knockdown of NL2, the expression level of KCC2 is significantly decreased, and GABA functional switch is significantly delayed during early development. Overexpression of shRNA-proof NL2 rescues both KCC2 reduction and delayed GABA functional switch induced by NL2 shRNAs. Moreover, NL2 appears to be required to maintain GABA inhibitory function even in mature neurons, because knockdown NL2 reverses GABA action to excitatory. Gramicidin-perforated patch clamp recordings confirm that NL2 directly regulates the GABA equilibrium potential. We further demonstrate that knockdown of NL2 decreases dendritic spines through down-regulating KCC2. CONCLUSIONS: Our data suggest that in addition to its conventional role as a cell adhesion molecule to regulate GABAergic synaptogenesis, NL2 also regulates KCC2 to modulate GABA functional switch and even glutamatergic synapses. Therefore, NL2 may serve as a master regulator in balancing excitation and inhibition in the brain.